Schools' Attitudes Towards Single Parents: Experimental Evidence - Luis Diaz-Serrano; Sabine Flamand (Institute of Labor Economics (IZA), 2020)
Single parenthood is on the rise everywhere in the world. While previous studies show that acceptance of single-parent households is increasing, some authors point out that single-parent families are often considered as a reality rather than as an ideal. This circumstance may cause negative attitudes towards single parents, who are also among the most vulnerable groups of society. Motivated by these findings, we study whether schools are more reluctant to interact with single parents than with heterosexual couples. We conduct a field experiment with schools during the children's pre-registration period. We create three types of fictitious families (heterosexual couple, single mother and single father) and send e-mails to schools in which the family structure is made explicit. Our results indicate that single parents benefit from positive discrimination. Schools are more prone to interact with single parents than with heterosexual couples. Further, single mothers receive more answers than single fathers.
Keywords: I24; I29; 330; single parents; schools; discrimination; field experiment; children